DEVELOPMENT OF THE UNIVERSAL ALGORITHM FOR THE AIRSPACE CONFLICTS RESOLUTION WITH AN AIRPLANE EN-ROUTE - N. A. Petrov (Научный вестник МГТУ ГА)
The paper outlines the formulation and solution of the problem of an airplane trajectory control within dynamically changing flight conditions. Physical and mathematical formulation of the problem was justified and algorithms were proposed to solve it using modern automated technologies.